Evaluating the tropical reservoir health by using the index of biotic integrity as a management tool for resource conservation planning - Xeai, Li Chai; Rohasliney, Hashim; Kamaruddin, I.S. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Biotic Integrity index (IBI) is widely utilized for biomonitoring in aquatic ecosystems, especially in assessing aquatic ecosystem health worldwide. Environmental changes significantly impact the aquatic ecosystem’s health of Subang Reservoir, which consequently affects the aquatic biodiversity. This study was conducted to determine its ecosystem’s health by assessing the IBI of freshwater fish in Subang Reservoir. In this study, thirty-four metrics were firstly selected as candidate metrics, and later, these thirty-four metrics underwent several statistical tests such as range, responsiveness, redundancy, and metrics scoring to screen and select the most appropriate metrics. A final eight metrics were selected after the statistical analysis, and a total score of 24 indicated that the Subang Reservoir’s ecosystem shows some stress due to an imbalanced fish guild. This showed that the ecosystem’s health of Subang Reservoir is in fair condition. This is because of the limitation of fish entering Subang Reservoir. The implementation of biomonitoring can be improved by modifying and selecting the most appropriate techniques, and the usage of biomonitoring can be increased in Malaysia’s freshwater ecosystems. The result reported in this study can be used as a scientific base data for implementing biomonitoring.